PDPN+ CAFs facilitate the motility of OSCC cells by inhibiting ferroptosis via transferring exosomal lncRNA FTX - Li, Yaoyin; Ma, Zeyi; Li, Weiyu; Xu, Xiaoqing; Shen, Peiqi; Zhang, Si-en; Cheng, Bin; Xia, Juan (Cell death & disease, 2023)
Cancer-associated fibroblasts (CAFs) are abundant and heterogeneous in tumor microenvironment (TME). Cross-talk between cancer cells and CAFs results in cancer progression. Here, we demonstrated that a distinct cancer-associated fibroblasts subset with podoplanin (PDPN) positive expression (PDPN + CAFs) was correlated with poor survival in oral squamous cell carcinoma (OSCC). PDPN + CAFs promoted the progression of OSCC by transferring exosomal lncRNA FTX to OSCC cells. Mechanically, FTX bound to flap endonuclease-1 (FEN1), forming an RNA‒protein complex. FTX enhanced promoter demethylation of FEN1 by recruiting ten-eleven translocation-2 (TET2). In addition, FTX/FEN1 axis promoted OSCC cells motility by inhibiting ferroptosis. In xenograft experiments, RSL-3, a ferroptosis-inducing agent, suppressed the tumorigenesis potential of FEN1-overexpressed OSCC cells. Furthermore, Acyl-CoA synthetase long-chain family member 4 (ACSL4) was confirmed to participate in the motility promotion induced by FEN1 overexpression. FEN1 could bind to promoter region of ACSL4 and then inhibit ferroptosis in OSCC cells. Our study reveals that PDPN + CAFs promote the invasiveness of OSCC cells by inhibiting ferroptosis through FTX/FEN1/ACSL4 signaling cascade. PDPN + CAFs may serve as a novel potential therapeutic target for OSCC.